Modern legislative Ijtihad: the need for a holistic approach - Haneef, Sayed Sikandar Shah (LexisNexis, 2009)
Ijtihad as a creative intellectual process initially led to the dynamic growth and authentic evolution of Islamic law. Nevertheless with the ascendancy of taqlid its role, by and large was confined to providing legal responses (fatawa) to novel issues. With the emergence of modern nation states, the calls for reinstating the place of ijtihad amidst attempts at Islamization of laws to a great extent provided the impetus for proclamation of Islamic legislations in most part of the Muslim world. However, a cursory look at the existing legislations reveals that the role of ijtihad was some what downplayed. In consequence, modern application of Islamic laws are said to be plagued with many pitfalls and flaws. This paper, therefore, argues that the restoration of multi-faceted role of ijtihad would fix these problems in all fields of the law particularly in the area of Islamic criminal law and personal law of status.